2016
DOI: 10.1128/jcm.02744-15
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Cutoff and Accuracy of an IgM Enzyme-Linked Immunosorbent Assay for Diagnosis of Acute Scrub Typhus in Northern Thailand: an Alternative Reference Method to the IgM Immunofluorescence Assay

Abstract: The enzyme-linked immunosorbent assay (ELISA) has been proposed as an alternative serologic diagnostic test to the indirect immunofluorescence assay (IFA) for scrub typhus. Here, we systematically determine the optimal sample dilution and cutoff optical density (OD) and estimate the accuracy of IgM ELISA using Bayesian latent class models (LCMs). Data from 135 patients with undifferentiated fever were reevaluated using Bayesian LCMs. Every patient was evaluated for the presence of an eschar and tested with a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…In the case of scrub typhus, our previous report showed that the serum antibody level of some patients was only elevated against limited serotypes, whereas that of most patients was elevated against all serotypes [7]. In some previous studies conducted outside of Japan, serological diagnostic methods such as ELISA were evaluated using only certain reference serotypes that did not include some of the most prevalent serotypes in Japan [8, 9], which can show wider variation than those of other countries. Accordingly, the sera from patients infected with a different serotype in Japan might not react to the serotypes used in these methods tested in previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of scrub typhus, our previous report showed that the serum antibody level of some patients was only elevated against limited serotypes, whereas that of most patients was elevated against all serotypes [7]. In some previous studies conducted outside of Japan, serological diagnostic methods such as ELISA were evaluated using only certain reference serotypes that did not include some of the most prevalent serotypes in Japan [8, 9], which can show wider variation than those of other countries. Accordingly, the sera from patients infected with a different serotype in Japan might not react to the serotypes used in these methods tested in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the serum antibody level of the patient will only be elevated against a specific serotype and not in response to the other serotypes. These facts clearly suggest that five or more strains should be used in serological tests of scrub typhus in Japan, although some previous reports from other countries used only a few standard strains in serological tests [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti- O. tsutsugamushi IgG can persist leading to high RDT false-positive rates in endemic areas, for which assay adjustments might be required. Currently available RDTs are immunochromatographic or semiquantitative dot-blot assays, increasingly incorporating recombinant antigens, allowing greater standardization, and simple readout for point-of-care testing in resource-constrained settings [ 16 , 35 38 ].…”
Section: Scrub Typhus Nucleic Acid Amplification Testsmentioning
confidence: 99%
“…The dissemination dynamics of Rickettsia and Orientia with their early limited bacteremic phase and subsequent appearance of antibodies have hindered the development of effective diagnostic tools for targeted early antirickettsial therapy. Especially in disease endemic areas, the occurrence of high background antibody titers poses an additional challenge to the already difficult serodiagnosis [ 16 , 17 ▪▪ , 18 , 19 ]. More hurdles involve translating promising technologies with high analytical sensitivity and specificity into clinically useful tests [ 2 , 20 ▪ ].…”
Section: Introductionmentioning
confidence: 99%